Method for reducing interface resistance of aluminum foil-carbon coating layer
By using an oxygen-depleted atmosphere or an inert atmosphere for drying and first drying in the aluminum foil carbon coating production process, the oxidation of the surface of the aluminum foil is avoided, the problem of increasing the interface resistance between the carbon coating layer and the aluminum foil is solved, and the lithium battery is significantly reduced internal resistance.
Patent Information
- Application Number
- CN202311831960.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2024-12-13
AI Technical Summary
During the traditional aluminum foil carbon coating production process, the baking and drying process causes the aluminum foil to oxidize again, forming an alumina film, increasing the interface resistance between the carbon coating layer and the aluminum foil, and thus increasing the internal resistance of the lithium battery.
After the sodium hydroxide cleaning, the drying is carried out using an oxygen-depleted atmosphere or an inert atmosphere and the first drying after the first side is coated with conductive paste, to avoid the aluminum oxide film being formed on the surface of the aluminum foil and ensure that the carbon coating layer is in direct contact with the aluminum.
It effectively reduces the interface resistance of the aluminum foil-carbon coating layer, reduces the internal resistance of the lithium battery, and improves the performance of the battery.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery foils, and in particular relates to a processing method for reducing the interface resistance of an aluminum foil-carbon coating layer. Background Art
[0002] Lithium-ion batteries are widely used in many fields such as automobiles and mobile phones due to their high energy density. The components of lithium batteries mainly include positive and negative electrode active materials, electrolytes, separators, and positive and negative electrode current collectors. At present, aluminum foil, copper foil, composite aluminum foil, composite copper foil, especially carbon-coated aluminum foil, carbon-coated copper foil, composite carbon-coated aluminum foil, and composite carbon-coated copper foil with carbon coating on the surface are the main materials used to transmit electrons. Traditional aluminum foil or copper foil current collectors have the problem of large interface resistance, while carbon-coated current collectors can change the interface resistance and improve the charging and discharging of batteries.
[0003] At present, most of the carbon coating production lines are based on the coating production process and equipment of the plastic and printing and dyeing industries, and are reasonably improved and perfected to produce carbon coated foil. The main production process of aluminum foil carbon coating is: aluminum foil unwinding - cleaning - baking - aluminum foil one side coating - drying - aluminum foil other side coating - drying - winding.
[0004] The above cleaning process generally uses sodium hydroxide solution for cleaning, which has the following effects: removing residual rolling oil on the surface of the foil, cleaning the oxide film on the surface of the aluminum foil, and slightly corroding the surface of the aluminum foil, thereby increasing the roughness of the surface of the aluminum foil and improving the adhesion of the coating slurry.
[0005] The process of coating the carbon coating on both sides of the aluminum foil is as follows: the aluminum foil is conveyed through a rotating roller at a certain linear speed and wrap angle, a coating roller is arranged parallel to the rotating roller and rotates in the opposite direction to the rotating roller, a part of the circumferential roller surface of the coating roller is immersed below the slurry liquid level of the conductive slurry (hereinafter also referred to as slurry or conductive carbon slurry), and the slurry is continuously brought up by the slurry storage effect of the surface pattern during rotation, and the slurry is evenly spread on the surface of the coating roller to form a slurry layer, and another part of the circumferential roller surface of the coating roller is slightly in contact with the aluminum foil conveyed by the rotating roller, and the slurry layer is continuously and evenly transferred to the aluminum foil during contact, and its principle is essentially the gravure printing principle. After the slurry is coated on the surface of the aluminum foil, it is dried with hot air to evaporate the water and other solvents in the slurry, and the polymer adhesive, conductive carbon black, conductive graphite, etc. in the slurry are dried and solidified and firmly adhered to the surface of the aluminum foil to form a carbon coating layer. After the coating and drying are completed on one side of the aluminum foil, the other side of the aluminum foil is coated and dried. During coating, the aluminum foil is transported by the rotating roller, so only the side of the aluminum foil that is not in contact with the rotating roller can be coated each time, and the slurry coating on one side of the aluminum foil must be dried before coating the other side. Both sides of the aluminum foil cannot be coated at the same time, because the side in contact with the rotating roller cannot contact the coating roller. It is also not possible to coat both sides of the aluminum foil successively and then dry the slurry on both sides at once, because when coating both sides of the aluminum foil successively, the first coated side will be in contact with the rotating roller surface of the aluminum foil during the subsequent coating, and there is a certain friction at the contact between the aluminum foil and the rotating roller. If there is no friction, the aluminum foil will not be driven by the rotating roller, and the friction will destroy the slurry coating that has been formed. After the finished carbon-coated aluminum foil is sent to the lithium battery manufacturer, the manufacturer will apply the lithium iron phosphate coating on the carbon-coated aluminum foil as the lithium battery current collector. The internal current of the lithium battery will pass through the lithium iron phosphate layer, the carbon coating layer, and the aluminum foil in turn and be transmitted to the outside of the battery. Therefore, how to reduce the interface resistance between the lithium iron phosphate layer and the carbon coating layer, and how to reduce the interface resistance between the carbon coating layer and the aluminum foil are of great significance to reducing the overall current collector resistance. Among them, how to reduce the interface resistance between the carbon coating layer and the aluminum foil is a technical problem that carbon-coated aluminum foil manufacturers must always continue to improve.
[0006] The present invention aims to further reduce the interface resistance between the carbon coating layer and the aluminum foil by improving the production process of the carbon coated aluminum foil. Summary of the invention
[0007] A first aspect of the present invention provides a method for reducing the interface resistance of an aluminum foil-carbon coating layer, the method comprising the following steps:
[0008] (1) treating the aluminum foil with a sodium hydroxide solution, washing with water, and drying;
[0009] (2) After coating one side of the aluminum foil with the conductive paste, first drying is performed in an oxygen-deficient atmosphere or an inert atmosphere to fix the first carbon coating layer to the side of the aluminum foil;
[0010] (3) Then, the other side of the aluminum foil is coated with a conductive paste and dried for a second time to fix the second carbon coating layer to the other side of the aluminum foil.
[0011] Preferably, in step (2), the oxygen content in the oxygen-depleted atmosphere is less than 21%, and the inert atmosphere is selected from a nitrogen atmosphere, a carbon dioxide atmosphere, a hydrogen atmosphere or a combination thereof.
[0012] The oxygen-deficient atmosphere refers to an atmosphere in which the volume content of oxygen is lower than 21%, such as lower than 15%, lower than 10%, lower than 8%, lower than 5%, or lower than 3%.
[0013] Preferably, in step (2), the first drying temperature is 40 to 100 degrees Celsius and the drying time is 0.5 to 30 minutes.
[0014] Preferably, the conductive paste contains conductive carbon black.
[0015] Preferably, in step (1), the concentration of the sodium hydroxide solution is 20 to 50 g / L, and the temperature is 25 to 60 degrees Celsius. The treatment time of the sodium hydroxide solution is 5 to 30 seconds.
[0016] Preferably, in step (1), the drying atmosphere is an oxygen-depleted atmosphere or an inert atmosphere, the oxygen content in the oxygen-depleted atmosphere is less than 21%, and the inert atmosphere is an atmosphere that does not react with metallic aluminum, including but not limited to nitrogen atmosphere, carbon dioxide atmosphere, hydrogen atmosphere or a combination thereof.
[0017] Preferably, the second drying is performed in air atmosphere. During the second drying process, since the carbon coating layer is fixed on one side of the aluminum foil and the conductive paste is coated on the other side, even if the drying atmosphere is air, oxygen cannot directly contact the aluminum and aluminum oxide is not easily generated.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. In the process of "aluminum foil unwinding - cleaning - baking - coating one side of aluminum foil - drying - coating the other side of aluminum foil - drying - winding", the baking and two drying processes in the prior art generally use hot air drying process. Hot air directly uses hot air.
[0020] The prior art has never realized that the baking or drying process will cause aluminum to regenerate aluminum oxide. Specifically, the prior art has never realized the following phenomenon: 1. Sodium hydroxide is used to clean the oxide film on the surface of the aluminum foil, so that the metal aluminum is exposed, but in the subsequent baking process, the atmosphere is air and the temperature is high, and the aluminum is oxidized to aluminum oxide again. Then the subsequent secondary coating is completely coated on the aluminum oxide. 2. Even if the baking process is under oxygen-deficient conditions, aluminum oxide will not be generated. In the drying process between "coating one side of the aluminum foil-drying-coating the other side of the aluminum foil", the temperature is high. Since the other side of the aluminum foil has not been coated with conductive slurry, the aluminum on its surface is easy to react with oxygen in high-temperature air (i.e. hot air) to regenerate aluminum oxide. Therefore, the other side of the aluminum foil that has not been coated with conductive slurry forms an aluminum oxide film during this drying process. After that, the coating on the other side of the aluminum foil is actually a coating on this aluminum oxide film, and the carbon coating layer after the slurry is dried is actually in contact with aluminum oxide rather than aluminum. Finally, lithium iron phosphate is coated on both sides of the aluminum foil coated with conductive slurry to obtain a pole piece. Therefore, the structure of the pole piece is: lithium iron phosphate-carbon coating layer-aluminum-aluminum oxide-carbon coating layer-lithium iron phosphate. The presence of aluminum oxide increases the interface contact resistance, which increases the internal resistance of the battery.
[0021] The present application is the first to realize that the baking or drying process will cause aluminum to regenerate aluminum oxide. Therefore, the present application avoids the problem of aluminum oxide film regeneration on the surface of aluminum foil during the drying and first drying processes by simultaneously controlling the atmosphere in the drying process after sodium hydroxide cleaning and the first drying process after the conductive paste is coated on the first surface to be an oxygen-deficient atmosphere or an inert atmosphere. Therefore, the problem of increased resistance of carbon-coated aluminum foil and increased interface resistance of the electrode sheet is solved.
[0022] 2. Compared with the drying process after sodium hydroxide cleaning and the first drying process after coating the conductive paste on the first side, in which the atmosphere is air atmosphere and other conditions remain unchanged, the carbon-coated aluminum foil product obtained by the method of the present application reduces the interface resistance of the aluminum foil-carbon coating layer. DETAILED DESCRIPTION
[0023] The present invention is described below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. Experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to the conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified. The raw materials required in the following examples and comparative examples are all commercially available.
[0024] Aluminum foil was purchased from Tianshan Aluminum Group Co., Ltd. Conductive carbon paste was from Guangdong Bohai Chemical Technology Co., Ltd.
[0025] Example 1
[0026] A method for reducing the interface resistance of aluminum foil-carbon coating layer, the method comprising the following steps:
[0027] (1) Aluminum foil pretreatment:
[0028] Take a single layer of 13μm thick aluminum foil roll and unwind it. After unwinding, put it into the cleaning tank to clean the surface of the aluminum foil for 20s;
[0029] The cleaning tank contains a sodium hydroxide solution with a concentration of 20 g / L and a temperature of 60°C;
[0030] During the cleaning process, sodium hydroxide can remove oil stains and oxide film on the surface of the aluminum foil, and at the same time corrode the surface of the aluminum foil to increase the roughness of the surface of the aluminum foil and improve the adhesion of the conductive paste.
[0031] The cleaned aluminum foil is washed with water and passed through a squeeze roller, and then enters a drying chamber for electric heating and drying. The drying chamber is filled with a nitrogen atmosphere to prevent aluminum oxidation. The temperature in the drying chamber is controlled at 76°C and the drying time is 3 minutes.
[0032] (2) coating one side of the aluminum foil obtained in step (1) with a conductive paste using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then performing a first drying;
[0033] The first drying method in step (2) is as follows: electric heating drying is performed in a drying chamber, a nitrogen atmosphere is provided in the drying chamber to prevent oxidation of aluminum, the temperature in the drying chamber is controlled to be 80° C., and the drying time is 2 min.
[0034] (3) Then, the other side of the aluminum foil is continuously coated with the conductive slurry using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then a second drying is performed to obtain a treated carbon-coated aluminum foil product.
[0035] The second drying method in step (3) is as follows: drying in a drying chamber, introducing hot air into the drying chamber, controlling the temperature in the drying chamber to 80° C., and drying time to 2 min.
[0036] Example 2
[0037] A method for reducing the interface resistance of aluminum foil-carbon coating layer, the method comprising the following steps:
[0038] (1) Aluminum foil pretreatment:
[0039] Take a single layer of 13μm thick aluminum foil roll and unwind it. After unwinding, put it into the cleaning tank to clean the surface of the aluminum foil for 10s;
[0040] The cleaning tank contains a sodium hydroxide solution with a concentration of 30 g / L and a temperature of 30°C;
[0041] During the cleaning process, sodium hydroxide can remove oil stains and oxide film on the surface of the aluminum foil, and at the same time corrode the surface of the aluminum foil to increase the roughness of the surface of the aluminum foil and improve the adhesion of the slurry.
[0042] The cleaned aluminum foil is washed with water and passed through a squeeze roller, and then enters a drying chamber for electric heating and drying. The drying chamber is filled with a carbon dioxide atmosphere to prevent aluminum oxidation. The temperature in the drying chamber is controlled at 90°C and the drying time is 1 minute.
[0043] (2) coating one side of the aluminum foil obtained in step (1) with a conductive paste using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then performing a first drying;
[0044] The first drying method in step (2) is as follows: use a drying chamber for electric heating drying, the drying chamber is filled with a carbon dioxide atmosphere to avoid oxidation of aluminum, the temperature in the drying chamber is controlled to 90° C., and the drying time is 1 min.
[0045] (3) Then, the other side of the aluminum foil is continuously coated with the conductive slurry using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then a second drying is performed to obtain a treated carbon-coated aluminum foil product.
[0046] The second drying method in step (3) is as follows: drying in a drying chamber, introducing hot air into the drying chamber, controlling the temperature in the drying chamber to 90° C., and drying time to 1 min.
[0047] Example 3
[0048] A method for reducing the interface resistance of aluminum foil-carbon coating layer, the method comprising the following steps:
[0049] (1) Aluminum foil pretreatment:
[0050] Take a single layer of 13μm thick aluminum foil roll and unwind it. After unwinding, put it into the cleaning tank to clean the surface of the aluminum foil for 15s;
[0051] The cleaning tank contains a sodium hydroxide solution with a concentration of 25 g / L and a temperature of 45°C;
[0052] During the cleaning process, sodium hydroxide can remove oil stains and oxide film on the surface of the aluminum foil, and at the same time corrode the surface of the aluminum foil to increase the roughness of the surface of the aluminum foil and improve the adhesion of the slurry.
[0053] The cleaned aluminum foil is washed with water and passed through a squeeze roller, and then enters a drying chamber for electric heating and drying. The drying chamber is filled with hydrogen atmosphere to avoid oxidation of aluminum. The temperature in the drying chamber is controlled at 80°C and the drying time is 1 minute.
[0054] (2) coating one side of the aluminum foil obtained in step (1) with a conductive paste using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then performing a first drying;
[0055] The first drying method in step (2) is as follows: electric heating drying is performed in a drying chamber, a hydrogen atmosphere is provided in the drying chamber to prevent oxidation of aluminum, the temperature in the drying chamber is controlled to be 80° C., and the drying time is 1 min.
[0056] (3) Then, the other side of the aluminum foil is continuously coated with the conductive slurry using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then a second drying is performed to obtain a treated carbon-coated aluminum foil product.
[0057] The second drying method in step (3) is as follows: drying in a drying chamber, introducing hot air into the drying chamber, controlling the temperature in the drying chamber to 80° C., and drying time to 1 min.
[0058] Example 4
[0059] A method for reducing the interface resistance of aluminum foil-carbon coating layer, the method comprising the following steps:
[0060] (1) Aluminum foil pretreatment:
[0061] Take a single layer of 13μm thick aluminum foil roll and unwind it. After unwinding, put it into the cleaning tank to clean the surface of the aluminum foil for 5s;
[0062] The cleaning tank contains a sodium hydroxide solution with a concentration of 50 g / L and a temperature of 40°C;
[0063] During the cleaning process, sodium hydroxide can remove oil stains and oxide film on the surface of the aluminum foil, and at the same time corrode the surface of the aluminum foil to increase the roughness of the surface of the aluminum foil and improve the adhesion of the slurry.
[0064] The cleaned aluminum foil is washed with water and passed through a squeeze roller, and then enters a drying chamber for drying. The temperature in the drying chamber is controlled at 76°C, and the oxygen content is controlled at 3% to significantly reduce the oxidation of aluminum. The drying time is 3 minutes.
[0065] (2) coating one side of the aluminum foil obtained in step (1) with a conductive paste using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then performing a first drying;
[0066] The first drying method in step (2) is as follows: drying in a drying chamber, with hot air in the drying chamber, the temperature in the drying chamber is controlled to be 76° C., the oxygen content is controlled to be 3% to significantly reduce the oxidation of aluminum, and the drying time is 3 minutes;
[0067] (3) Then, the other side of the aluminum foil is continuously coated with the conductive slurry using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then a second drying is performed to obtain a treated carbon-coated aluminum foil product.
[0068] The second drying method in step (3) is as follows: drying in a drying chamber, introducing air into the drying chamber, controlling the temperature in the drying chamber to 76° C., and drying time to 3 min.
[0069] Example 5
[0070] A method for reducing the interface resistance of aluminum foil-carbon coating layer, the method comprising the following steps:
[0071] (1) Aluminum foil pretreatment:
[0072] A single layer of 13 μm thick aluminum foil roll is unwound and then placed in a cleaning tank to clean the surface of the aluminum foil for 60 seconds.
[0073] The cleaning tank contains a sodium hydroxide solution with a concentration of 20 g / L and a temperature of 60°C;
[0074] During the cleaning process, sodium hydroxide can remove oil stains and oxide film on the surface of the aluminum foil, and at the same time corrode the surface of the aluminum foil to increase the roughness of the surface of the aluminum foil and improve the adhesion of the slurry.
[0075] The cleaned aluminum foil is washed with water and passed through a squeeze roller and then placed in a drying chamber for drying. The temperature in the drying chamber is controlled at 60°C and the oxygen content is 5% to significantly reduce the oxidation of aluminum. The drying time is 2 minutes.
[0076] (2) coating one side of the aluminum foil obtained in step (1) with a conductive paste using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then performing a first drying;
[0077] The first drying method in step (2) is as follows: drying in a drying chamber, controlling the temperature in the drying chamber to 60° C., the oxygen content to 5% to significantly reduce the oxidation of aluminum, and the drying time to 2 minutes.
[0078] (3) Then, the other side of the aluminum foil is continuously coated with the conductive slurry using a gravure roll coater, with a coating thickness of 0.5 μm and a coating speed of 100 m / min, and then a second drying is performed to obtain a treated carbon-coated aluminum foil product.
[0079] The second drying method in step (3) is as follows: drying in a drying chamber, introducing air into the drying chamber, controlling the temperature in the drying chamber to 60° C., and drying time to 2 min.
[0080] Comparative Example 1
[0081] The nitrogen gas in the first drying in step (2) of Example 1 was replaced by air. Other conditions remained unchanged.
[0082] At this time, since the drying in step (1) is still in a nitrogen atmosphere, step (2) is to apply the conductive paste on the aluminum surface. Since the first drying in step (2) is in an air atmosphere, the other side of the aluminum foil that is not coated is oxidized to aluminum oxide, resulting in the coating of the conductive paste in step (3) being on the aluminum oxide surface.
[0083] Comparative Example 2
[0084] The nitrogen gas in the drying step of step (1) of Example 1 was replaced by air, and the nitrogen gas in the first drying of step (2) was replaced by air. Other conditions remained unchanged.
[0085] At this time, since the drying in step (1) is carried out in an air atmosphere, aluminum oxide is generated on the aluminum surface during the drying process. Therefore, the coating in steps (2) and (3) is performed on the aluminum oxide surface.
[0086] Comparative Example 3
[0087] The oxygen content in the first drying of step (2) of Example 4 was changed from 3% to 21%, while other conditions remained unchanged.
[0088] In this comparative example 3, the conductive paste applied in step (2) is mainly on the aluminum surface (but there is also a small amount of aluminum oxide film). During the first drying process of step (2), the aluminum on the other side of the aluminum foil is oxidized to aluminum oxide, so the conductive paste applied in step (3) is applied on the aluminum oxide surface.
[0089] Comparative Example 4
[0090] The oxygen content in the drying step of step (1) of Example 4 was changed from 3% to 21%, and the oxygen content in step (2) was changed from 3% to 21%. Other conditions remained unchanged. In this comparative example 4, since the oxygen content in the drying process of step (1) was 21%, aluminum oxide was generated on the aluminum surface during the drying process. Therefore, the coating of steps (2) and (3) was both on the aluminum oxide surface.
[0091] Performance Testing:
[0092] The carbon-coated aluminum foil products obtained in the above examples and comparative examples were sampled to obtain 20 cm 2 Carbon coated aluminum foil samples of different sizes.
[0093] The resistance of the carbon-coated aluminum foil samples of the above-mentioned embodiments and comparative examples was tested using a probe tester. The above test results are shown in Table 1. As can be seen from Table 1, the resistance of embodiments 1-5 is less than that of comparative examples 1-4. This shows that: 1. An oxygen-poor atmosphere or an inert atmosphere is used in the drying process after the aluminum foil is pretreated with a sodium hydroxide solution, so that aluminum oxide is not easily generated on both sides of the aluminum foil, thereby avoiding the problem of increased resistance of the carbon-coated aluminum foil and increased interface resistance of the electrode. 2. The present application also avoids the problem of aluminum oxide film being generated on the second side of the aluminum foil during this drying process by controlling the atmosphere in the first drying process after coating the conductive slurry on the first side to be an oxygen-poor atmosphere or an inert atmosphere. Therefore, the problem of increased resistance of the carbon-coated aluminum foil and increased interface resistance of the electrode is solved.
[0094] Table 1
[0095] Sample source Carbon-coated aluminum foil product resistance (unit: milliohm) Example 1 1.239 Example 2 1.336 Example 3 1.382 Example 4 1.529 Example 5 1.558 Comparative Example 1 2.084 Comparative Example 2 2.717 Comparative Example 3 2.495 Comparative Example 4 3.452
Claims
1. A method for reducing the interface resistance of aluminum foil-carbon coating layer, characterized in that: The method comprises the following steps: (1) treating the aluminum foil with a sodium hydroxide solution, washing with water, and drying; (2) After coating one side of the aluminum foil with the conductive paste, first drying is performed in an oxygen-deficient atmosphere or an inert atmosphere to fix the first carbon coating layer to the side of the aluminum foil; (3) Then, the other side of the aluminum foil is coated with a conductive paste and dried for a second time to fix the second carbon coating layer to the other side of the aluminum foil.
2. The method according to claim 1, characterized in that In step (2), the oxygen content in the oxygen-depleted atmosphere is less than 21%, and the inert atmosphere is selected from nitrogen atmosphere, carbon dioxide atmosphere, hydrogen atmosphere or a combination thereof.
3. The method according to claim 1, characterized in that In step (2), the first drying temperature is 40 to 100 degrees Celsius.
4. The method according to claim 1, characterized in that: The conductive paste includes conductive carbon black.
5. The method according to claim 1, characterized in that In step (1), the concentration of the sodium hydroxide solution is 20-50 g / L and the temperature is 25-60 degrees Celsius.
6. The method according to claim 1, characterized in that In step (1), the drying atmosphere is an oxygen-deficient atmosphere or an inert atmosphere, the oxygen content in the oxygen-deficient atmosphere is less than 21%, and the inert atmosphere is selected from a nitrogen atmosphere, a carbon dioxide atmosphere, a hydrogen atmosphere or a combination thereof.
7. The method according to claim 1, characterized in that The second drying is in air atmosphere.
